Procedure for executing administrative sanctions - Villacreses Valle, Jaime Andrés (Universidad Nacional del Litoral, 2019)
The purpose of this investigation is to analyze the justification of the existence of means and procedure of forced execution of the administrative sanctions before the voluntary breach of the provisions in the sanctioning administrative act by the offender. In this sense, it is important to determine from when the execution procedure should be initiated, what are the means of forced execution, identify the limits and guarantees in the exercise of the administrative self-guardianship and the possibility of challenge in judicial headquarters of the administrative acts of execution.